Ostatni król Rzeczypospolitej - Fras, Zbigniew (1952-1998).; Zamoyski, Adam (1949- ). (1995)
Recenzja książki: Ostatni król Polski / Adam Zamoyski. Warszawa, 1994.
Tytuł nagłówkowy.
Keywords: Książki -- recenzje -- 1990-.